Critical Analysis of Gen-Z’s Hedonistic Consumer Behavior through the Lens of Islamic Ethical Consumption - Ahmad Maulidizen; Yogi Permana Adi Citra; Muhammad Diaz Wahyu Darmansyah (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2025)
This study critically examines the phenomenon of hedonistic consumerism among Generation Z through the perspective of ethical consumption in Islam. In the digital era dominated by instant lifestyles, technology, and the massive influence of social media, Generation Z is increasingly exposed to consumerist values oriented towards instant gratification. This phenomenon often contradicts Islamic principles of simplicity, responsibility, justice, and spiritual awareness in shopping and using goods and services. The main objective of this study is to analyze the extent to which the developing hedonistic consumption patterns deviate from Islamic consumption ethics and to explore the factors driving this trend. This study uses a qualitative approach based on literature review, referring to classical Islamic sources, contemporary fatwas, and modern literature on the consumption behavior of the younger generation and Islamic economics. The analysis results indicate a widening gap between Generation Z's consumption behavior and Islamic ethical norms. Influencing factors include social pressure in the digital space, manipulative marketing strategies, low financial literacy, and the commodification of identity that makes consumption a symbol of social status. However, this study also found positive trends that can be used as opportunities for reorientation, such as increasing awareness of halal lifestyles, a growing preference for sustainable products, and the emergence of more ethical marketing strategies based on Islamic values. Thus, Islamic ethical consumption can be revitalized through strengthened education, media involvement, and family guidance, so that Generation Z's consumption behavior can be re-aligned with moral, spiritual, and equitable Islamic economic principles. This study emphasizes the importance of integrating religious awareness with modern consumption practices in an effort to address the challenges of global consumerism.